The role of microRNAs in the resistance to colorectal cancer treatments - Amirkhah, R; Farazmand, A; Irfan-Maqsood, M; Wolkenhauer, O; Wolkenhauer, O; Schmitz, U (Cellular and Molecular Biology, 2015)
Colorectal cancer (CRC) is one of the leading cancer-related causes of death in the world. Several approaches such as surgery, chemotherapy, radiotherapy, targeted therapy, or combinations thereof have been used to treat CRC patients. However, the fact that many patients develop a drug resistance during the course of the treatment is a major obstacle. Understanding the mechanisms underlying resistance is critical in order to develop more effective targeted treatments. Recently, several studies have reported on the regulatory role of microRNAs (miRNAs) in the response to anti-cancer drugs and suggested them as a source of predictive biomarkers for the purpose of patient stratification and for the prognosis of treatment success. For example, overexpressing miR-34a, a master regulator of tumor suppression attenuates chemoresistance to 5-FU by downregulating silent information regulator 1 (SIRT1) and E2F3. MRX34, a miR-34a replacement is the first synthetic miRNA mimic to enter clinical testing. MiR-34a antagonizes cancer stemness, metastasis, and chemoresistance processes that are necessary for cancer viability. This example shows that miRNAs are coming into focus for the design of enhanced cancer therapies that aim to sensitise tumor cells for anti-cancer drugs. In this review, we provide an overview on the role of miRNAs in the resistance to current colorectal cancer therapies. Furthermore, we discuss the value of miRNAs as biomarkers for predicting chemosensitivity and their potential to enhance treatment strategies.